Reflective practice of early career teachers: Identifying and mitigating major instructional challenges - Saheeh Shafi (Journal of Global Education and Research)
This paper employs a qualitative descriptive research design to determine how early career teachers (ECTs) use reflective practices to identify and mitigate major instructional challenges in the context of Bangladeshi higher education. A questionnaire was given to 20 ECTs working in different universities to collect data on their reflective practices related to instructional challenges. Analysis of the responses of the ECTs to the questionnaire via thematic analysis revealed three major challenges: (a) inadequate logistic support, (b) diversity of students and pedagogical context, and (c) inadequate comprehension of the students. Solutions to these challenges include (a) three levels of collaboration, (b) context-specific measures, and (c) providing interesting and interactive materials. Various levels of reflection include the timing, depth, and content of reflection. The discussion of this paper provides the reasons for these challenges, possible solutions from the past experiences of ECTs, and implications for future teaching. Practical implications are also provided for policy-makers.